2012
DOI: 10.1002/cncy.21210
|View full text |Cite
|
Sign up to set email alerts
|

Should LSIL‐H be a distinct cytology category?

Abstract: BACKGROUND: The 2001 Bethesda System for gynecologic cervical cytology reporting classifies squamous intraepithelial lesions into low‐grade (LSIL) and high‐grade (HSIL) lesions. An intermediate term, “low‐grade squamous intraepithelial lesion, cannot exclude high‐grade squamous intraepithelial lesion (LSIL‐H),” has been used in a small percentage of LSIL cases. To the authors' knowledge, little is known regarding the human papillomavirus (HPV) status in patients with LSIL‐H. METHODS: A total of 808 SurePath sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Owens et al found a higher prevalence of hrHPV in LROH (100%) compared with ASC‐H (59%). Similarly, Shidham et al reported 94% positivity for hrHPV for LROH/LSIL‐H (34/88) cases; Zhou et al also found the prevalence of hrHPV in LROH (92%), closer to HSIL (91%), when compared to LSIL (74%) and ASC‐H (78%). Barron et al reported hrHPV testing in 496 patients with LROH with a 90.5% positive rate, lower than HSIL (95.7%) and higher than ASC‐H (54.3%).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Owens et al found a higher prevalence of hrHPV in LROH (100%) compared with ASC‐H (59%). Similarly, Shidham et al reported 94% positivity for hrHPV for LROH/LSIL‐H (34/88) cases; Zhou et al also found the prevalence of hrHPV in LROH (92%), closer to HSIL (91%), when compared to LSIL (74%) and ASC‐H (78%). Barron et al reported hrHPV testing in 496 patients with LROH with a 90.5% positive rate, lower than HSIL (95.7%) and higher than ASC‐H (54.3%).…”
Section: Discussionmentioning
confidence: 88%
“…This terminology reflects the understanding of human papillomavirus (HPV) infection, the biological differences between these lesions and the significant impact on patient management. According to the 2014 American Society for Colposcopy and Cervical Pathology consensus guidelines, women with HSIL are treated with colposcopy and diagnostic excisional procedures, such as loop electrocautery excision procedure or cervical conisation; on the other hand, management of LSIL varies from repeat cytology/HPV cotesting to colposcopy, depending on factors such as age, pregnancy and HPV status …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations